Cathepsin B Is Required for NLRP3 Inflammasome Activation in Macrophages, Through NLRP3 Interaction - Chevriaux, Angélique; Pilot, Thomas; Derangère, Valentin; Simonin, Harmonie; Martine, Pierre; Chalmin, Fanny; Ghiringhelli, François; Rébé, Cédric (Frontiers in Cell and Developmental Biology, 2020)
The mechanisms leading to NLRP3 (NOD-leucine rich repeat and pyrin containing protein 3) inflammasome activation are still debated. It is well established that oligomerized NLRP3 interacts with ASC (Apoptosis associated Speck-like protein containing a CARD domain) which polymerizes into filaments recruiting procaspase-1, leading to its activation. However pathways triggering NLRP3 activation, such as potassium efflux, ROS production or lysosomal permeabilization, can be required or not, depending on the activators used. Here we proposed to evaluate the importance of Cathepsin B on NLRP3 inflammasome assembly and activation. Using Cathepsin B-/- BMDMs (Bone Marrow-Derived macrophages), we first show that Cathepsin B is required for caspase-1 activation, IL-1β production and ASC speck formation, upon treatment with different types of NLRP3 activators, i.e. ATP, nigericin or crystals. Moreover, in these conditions, Cathepsin B interacts with NLRP3 at the endoplasmic reticulum (ER) level. To conclude, different NLRP3 activators lead to Cathepsin B interaction with NLRP3 at the ER level and to subsequent caspase-1 activation.